Effect of Credit Risk on the Profitability of Banks Listed on The Ghana Stock Exchange - Israel Opoku Ayim; Oscar Opoku Agyemang (Garuda Prestasi Nusantara Consulting, 2021)
The study analysed the effect of credit risk on the profitability of banks listed on the Ghana Stock Exchange. Annual data of 8 out of the 9 banks listed on the Ghana Stock Exchange were used and a panel data regression model was used to analyse the financial reports of the selected banks. It was found that the profitability of banks listed on GSE is not influenced by Non-Performing Loans Ratio (NPLR), Cash Reserve Ratio (CRR), Asset Growth Ratio (AGR) and leverage ratio (LEV), however, Capital Adequacy Ratio (CAR) and cost per loan asset (CPLA) influence the profitability of banks. The result shows that 49.5% of change in profitability of banks listed on GSE is attributable to the independent variables in the model. The study recommended among other things that the Bank of Ghana (BoG) and other supervisors/regulators of the banking sector should focus on other profit indicators either than credit risk if they want to influence the profitability of banks. Also, management of banks listed on the Ghana Stock Exchange should pay attention to capital adequacy ratio (CAR) and Cost Per Loan Asset (CPLA) which have significant influence on profitability. Finally, future studies should consider the effect of liquidity risk, market risk or operational risk on profitability of banks listed on the GSE. Keywords: Credit risk, Profitability, Ghana Stock Exchange, Capital Adequacy Ratio, Non-Performing Loans Ratio